IMPLEMENTATION OF CUSTOMER RELATIONSHIP MANAGEMENT FOR SALES OF USED SHOES AT MZM SECOND BRANDED TANJUNGBALAI - Nur Madani Putri Siregar; Fauriatun Helmiah; Rohminatin Rohminatin (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Background : MZM SECOND BRANDED Tanjungbalai does not yet have a website facility that can promote used shoes and has difficulty storing customer data that has made transactions. Method : In carrying out this research, the researcher used qualitative research methods. This form of research is carried out through interviews or direct observation, aiming to describe a fact or a situation that exists in the place where the research is carried out. Result : From the implementation and testing results, it can be explained that the system designed at MZM SECOND BRANDED Tanjungbalai is a system that provides convenience for admins in data processing, such as inputting product data, product categories, and printing reports. Conclusion : the existence of MZM SECOND BRANDED Tanjungbalai CRM can increase satisfaction, where customers can make transactions and get information easily through the content on the MZM SECOND BRANDED website.